Gamification Design for Education in Learning Management System - Nurmanditya, Muhamad Iqbal (Multidisciplinary Applied Research and Innovation, 2021)
The COVID-19 pandemic has made teaching and learning activities in schools abolished and schools have started learning activities from home. Therefore, the suitable technology is the application of E-Learning using a Learning Management System with an acceptable level of acceptance. The students still get material even though they do not come to school. Learning Management System has developed many advantages, such as announcements, assessments, assignments and so on in the use of Learning Management System. However, its long-running implementation makes students bored and of course the level of their focus in front of the screen is reduced and distracted by things like games, because for students, games make them not bored. can be seen by measuring the fact that students have the opportunity to increase the level of desire to learn by seeing how difficult the material will be. From here they can classify materials and related tasks and learn more interactively because they explore the LMS system itself. Because the level of focus of students in viewing computer screens is not very good, it is necessary to be developed so that students can stay focused on learning activities. This research found the development by combining Learning Management System with game mechanism which is usually called Gamification. The application of Gamification itself has been applied to startups such as Grab and Gojek in increasing user activity, so the application in terms of Education can also be done with a system, namely Gamification for Education in the Learning Management System. It is also hoped that the application of gamification in system management learning is expected to contribute to science, especially educational technology.